Understanding Consonant Sound: The Key to Accurate Pronunciation - Maulidya, Amanah; Arsyah, Afifah; Jaariyah, A’inun; Lubis, Yani (EXCELLENCE: Journal of English and English Education, 2025)
This study investigates the role of consonant sounds in English pronunciation and their implications for language learning. Utilizing a qualitative study design, the research covers a sample of 30 non-native English speakers aged 18-30 and 10 English language teachers. Data is acquired through semi-structured interviews, focus group discussions, classroom observations, and audio analysis of recorded reading sessions. While acoustic analysis evaluates students' pronunciation accuracy, thematic analysis of interview transcripts finds recurrent themes pertaining to the comprehension and instruction of consonant sounds.The results demonstrate the difficulties students encounter when learning consonants and the efficient teaching methods teachers employ to overcome these difficulties. Consonants are crucial for communication, listening comprehension, and general language proficiency, according to the study. It also provides recommendations for curriculum development that focuses on pronunciation skills. Ultimately, this research contributes to a comprehensive understanding of consonant sounds in English, offering insights that benefit both language learners and educators, and enhancing the language learning experience.